Posted by **dd** on Saturday, July 13, 2013 at 9:26am.

x-y+z=3

2x-y+z=4

x+2y-z=-1

solve in Gaus-Jordan method

## Answer this Question

## Related Questions

- Pre-Calculus - Solve for x,y,z, & w using the Gauss-Jordan Elimination Method 5x...
- math - solve by the gauss-jordan method x+y+z=6 3x+2y-z=4 3x+2y+2z=11
- Math - Use the Gauss-Jordan method to solve the equation: 3x-5y-2z=-9 -4x+3y+z=...
- MATH - solve the system of linear equations using the Gauss- Jordan elimination ...
- Algebra - Use the Gauss-Jordan method to invert 1 0 0 2 -1 0 0 0 1 A1= 1 1 1 A2...
- math - What is the difference between Gauss Jordan method and the Echelon method
- Algebra - How would you solve this matrices using the Gauss-jordan elimination ...
- math-matrix - solve using the gauss-jordan method. x-2y+4z=7 -x+3y-z=-1 2x+y=-2...
- Finite Math - Discuss the differences between the echelon method and the gauss-...
- english - [Key: Jordan = Barbara Jordan] In "All Together Now", Jordan uses ...